PERPINDAHAN PANAS PADA MAKANAN BERPATI (KERUPUK UDANG) SELAMA PROSES PENYANGRAIAN MENGGUNAKAN PASIR SEBAGAI MEDIA PENGHANTAR PANAS - Susanna, Susanna; Jamaluddin P, Jamaluddin P; Kadirman, Kadirman (Universitas Negeri Makassar, 2017)
This research was aims to know the mechanism of heat transfer in starchy food during roasting process using sand as a medium for heat transfer. This research is experimental research, and the research samples were shrimp crackers roasted at the temperature of 120, 140 and 160 oC within roasting time of 10, 15, 20 and 25 seconds. During the roasting process, the temperature of sand and crackers was measured using a thermocouple to know the change in temperature that happened. The parameters being observed the temperature, water content of crackers and rate of heat transfer. The research results showed that during the roasting process, the changes of temperature, water content of the crackers and rate of heat transfer. The higher the temperature and the length of time roasting cause the temperature of the crackers to increase closer to the temperature of the sand with the decrease in the water content of crackers and increase in the rate of heat transfer